Disentangling of complex polymer dynamics under soft nanoscopic confinement. Issue 45 (15th October 2020) - Kuttich, Björn; Hoffmann, Ingo; Stühn, Bernd
Abstract : PEG confined to the core of a droplet phase microemulsion is located at the water/surfactant interface. Neutron spin echo spectroscopy allows to disentangle polymer from droplet dynamics. Under large confinement sizes accelerated dynamics are found. Abstract : We discuss the complex interplay between host and guest dynamics for a polymer in soft confinement by a droplet-phase microemulsion. Intermediate scattering functions obtained by neutron spin echo spectroscopy are first analysed by means of an effective diffusion coefficient. From its dependence on the absolute of the scattering vector q we concluded a sophisticated model for the systems dynamics taking both polymer and microemulsion contributions into account. Global fitting of this model to the intermediate scattering functions at all measured q -values and all investigated confinement sizes eventually allows for a precise disentangling of the pure polymer dynamics in confinement from the overlaying microemulsion dynamics. Validity of our approach is further supported by numerical random walk calculations.